Bentuk Penyajian Kesenian Didong Grup Musara Bintang di Desa Linung Bulen II Kecamatan Bintang Kabupaten Aceh Tengah - Yanti, Yunita Rahma; Wirandi, Rika; Ocktarizka, Tria (Jurnal Musik Etnik Nusantara, 2024)
This research is entitled "Forms of Presentation of the Didong Arts of the Musara Bintang Group in Linung Bulen II Village, Bintang District, Central Aceh Regency". The author examines the form of presentation of Didong art by the Musara Bintang Group in Linung Bulen II Village, Bintang District, Central Aceh Regency. The research method used is a descriptive qualitative approach. Data obtained in the field used observation, interview and documentation techniques.The theory used in this research is the presentation theory from Djelantik's theory which states that form is the basic element of manifestation. In the form of presentation, it means that form is a fundamental element of a performance. These elements include artists, musicians, seating formation, movement, songs presented, costumes, performance venue, and audience. Based on the results of research in presentation, Didong art is played by 15 people consisting of: 1 Ceh Apit (Ceh Companion), 1 Main Ceh, and 2 Penepok Pumu and 2 Penepok pillow splits, each of which acts as a pillow act, split pillow , and 9 players who act as penepok/penunung (followers). The Didong art performance consists of 9 stages, for the costumes the players wear black unity t-shirts with the words "Musara Bintang" written on the chest and wear a headband called Jembolang.